1996
DOI: 10.2134/agronj1996.00021962008800020010x
|View full text |Cite
|
Sign up to set email alerts
|

MODWht3: A Development‐Driven Wheat Growth Simulation

Abstract: Crop growth simulations are needed to help organize our knowledge of plant response to the environment for the purpose of assisting growers in management decisions, predicting impacts of land use decisions, and predicting the consequences of probable climatic variation. This paper describes the derivation, combination, and (where necessary) calibration of the models required to produce a simulation of the seasonal development and growth of winter wheat. The simulation provides appearance time and size estimate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(22 citation statements)
references
References 30 publications
3
16
0
Order By: Relevance
“…In order to do this, OSU needs to continue to evaluate and improve this technology to fit farmers and the environmental needs of our world. This approach is consistent with work showing the relationship between above ground plant dry weight and cumulative GDD (Rickman et al, 1996). Further analyses showed that a reliable INSEY could be obtained by dividing NDVI by the days from planting to sensing date (where GDD > 0) (Raun et al, 2002;Mullen et al, 2003).…”
Section: Introductionsupporting
confidence: 87%
“…In order to do this, OSU needs to continue to evaluate and improve this technology to fit farmers and the environmental needs of our world. This approach is consistent with work showing the relationship between above ground plant dry weight and cumulative GDD (Rickman et al, 1996). Further analyses showed that a reliable INSEY could be obtained by dividing NDVI by the days from planting to sensing date (where GDD > 0) (Raun et al, 2002;Mullen et al, 2003).…”
Section: Introductionsupporting
confidence: 87%
“…Another recurring quest in the wheat phenological research in recent decades has been to better understand the role of temperature and to improve the thermal time concept (Mcmaster, 1997). Most wheat phenological modeling is based on the concept of thermal time, which is further modified by factors such as photoperiod, water stress, nutrient stress, upper temperature thresholds, and varying base temperatures (Weir et al, 1984;Ritchie and Otter, 1985;Mcmaster et al, 1992;Rickman et al, 1996). Cabelguenne et al (1999) divided the wheat growth into 4 different phases in the EPICphase model to improve the simulation of biomass, HI, and other relevant processes.…”
Section: Inter Seasonal Variation Of the Crop Parametersmentioning
confidence: 99%
“…Several seeding date experiments conducted in the United Kingdom (Baker et al 1980) and in western Australia (Kirby and Perry 1987) have indicated that phyllochron was correlated with the rate of daylength change at emergence. This concept has been incorporated in some wheat simulation models (Weir et al 1984;Wilhelm et al 1993;Rickman et al 1996). However, more recently, researchers have found this correlation did not exist in growth rooms (Cao and Moss 1989b;Hay and Delecolle 1989) or in the field (Baker et al 1986;Hotsonyame and Hunt 1997).…”
Section: Factors Affecting Leaf Appearancementioning
confidence: 99%